2018
DOI: 10.3389/fneur.2018.00954
|View full text |Cite
|
Sign up to set email alerts
|

Blood Level of Glial Fibrillary Acidic Protein (GFAP) Does not Correlate With Disease Progression in a Rat Model of Familial ALS (SOD1G93A Transgenic)

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by specific loss of motor neurons in the spinal cord and brain stem. Currently, there are limited options for treating ALS and further investigation of the disease etiology and ALS disease progression need to be completed. There is an urgent need to identify biomarkers to detect and study disease progression in ALS. Glial fibrillary acidic protein (GFAP) is an intermediate filament protein that is expressed by a number of cells re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Such a reduction was previously identified by us and others in astrocytes from mSOD1 rodents [ 20 , 21 ], or after transfection with mSOD1 [ 104 ], and was shown to accelerate disease progression [ 105 ]. Elevated levels of GFAP were also not found in the blood of mSOD1 mice [ 106 ]. It was recently suggested that this aspect should not be considered, per se, an absolute marker of reactivity, or to represent cell altered functions when increased [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a reduction was previously identified by us and others in astrocytes from mSOD1 rodents [ 20 , 21 ], or after transfection with mSOD1 [ 104 ], and was shown to accelerate disease progression [ 105 ]. Elevated levels of GFAP were also not found in the blood of mSOD1 mice [ 106 ]. It was recently suggested that this aspect should not be considered, per se, an absolute marker of reactivity, or to represent cell altered functions when increased [ 107 ].…”
Section: Discussionmentioning
confidence: 99%